2004
DOI: 10.1097/01.fjc.0000133060.10597.3c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Endothelium-Dependent Vasodilation and the Antihypertensive Effect of Brazilian Red wine

Abstract: The mechanisms involved in the cardioprotector effect of red wine have not yet been completely elucidated but probably an endothelium-dependent vasodilator action may play a significant role in this effect. Experiments were undertaken to determine whether a Brazilian red wine (BRW) induces vasodilation in the mesenteric vascular bed (MVB) and an antihypertensive effect was also assessed in rats with NO-deficient hypertension. In MVB precontracted with norepinephrine, BRW (alcohol-free lyophilized) induces a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…However, since the addition of charybdotoxin plus apamin to L -NA further reduced relaxations to GSE, EDHF is also involved to some extent. The present findings are in agreement with previous ones indicating that GSE caused vasodilatation in the perfused rat mesenteric arterial bed by increasing the formation of NO and EDHF [17, 18]. Besides grape skin extracts, other grape-derived products, including red wine, red wine extracts, grape juices and grape seed extracts, have also been shown to cause endothelium-dependent relaxations involving NO and EDHF [9, 10, 13, 28, 29].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, since the addition of charybdotoxin plus apamin to L -NA further reduced relaxations to GSE, EDHF is also involved to some extent. The present findings are in agreement with previous ones indicating that GSE caused vasodilatation in the perfused rat mesenteric arterial bed by increasing the formation of NO and EDHF [17, 18]. Besides grape skin extracts, other grape-derived products, including red wine, red wine extracts, grape juices and grape seed extracts, have also been shown to cause endothelium-dependent relaxations involving NO and EDHF [9, 10, 13, 28, 29].…”
Section: Discussionsupporting
confidence: 93%
“…Recently, we have shown that chronic intake of the polyphenols contained in an alcohol-free lyophilized Brazilian red wine or in an alcohol-free grape skin extract (GSE) from Vitis labrusca reduced systolic, mean and diastolic arterial pressure in several experimental models of hypertension [16, 17]. Both types of extracts also caused endothelium-dependent vasodilation in the perfused rat mesenteric vascular bed by increasing the endothelial formation of both NO and EDHF [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Many evidences suggest that diet rich in polyphenols might be involved in protection against cardiovascular risk. 7 This beneficial effect of polyphenols may be due to many actions as antioxidant 8 that increases bioavailability of nitric oxide, vasodilation, 9 or antihypertensive 10 properties. In addition, recent results from our group demonstrated that ac xaí seed extract (ASE) as ac xaí skin extract have a potent endothelium-dependent vasodilator effect 11 and antihypertensive action.…”
Section: Introductionmentioning
confidence: 99%
“…One of the hallmarks of the hypertensive pathophysiological process is endothelium dysfunction provoked by excessive reactive oxygen species production and vascular inflammation [54]. Although numerous studies indicate that red wine and polyphenols present in wine induce an endothelium-dependent vasorelaxant effects [55,56,57], our results have shown that Fr 2 SySFV at concentrations of 0.01–1000 µg/mL induced concentration-dependent relaxation of isolated rat superior mesenteric rings pre-contracted with phenylephrine, an effect which was not attenuated by removal of ring endothelium. In a previous study with a lyophilized red wine from SFV, Luciano et al (2011) [25] demonstrated the vasorelaxant activity of the wine was significantly attenuated by endothelium removal.…”
Section: Discussionmentioning
confidence: 99%